2014
DOI: 10.3201/eid2009.140545
|View full text |Cite
|
Sign up to set email alerts
|

Incidence ofCronobacterspp. Infections, United States, 2003–2009

Abstract: During 2003–2009, we identified 544 cases of Cronobacter spp. infection from 6 US states. The highest percentage of invasive infections occurred among children <5 years of age; urine isolates predominated among adults. Rates of invasive infections among infants approximate earlier estimates. Overall incidence of 0.66 cases/100,000 population was higher than anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
98
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 11 publications
0
98
0
1
Order By: Relevance
“…These findings also corroborate those of a single hospital-based microbiological survey and outcomes for elderly stroke patients as reported previously. However, the highest incidence rate of invasive disease leading to sepsis and meningitis was more prevalent in infants (Patrick et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings also corroborate those of a single hospital-based microbiological survey and outcomes for elderly stroke patients as reported previously. However, the highest incidence rate of invasive disease leading to sepsis and meningitis was more prevalent in infants (Patrick et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Although the disease incidence is low, the mortality rate has been reported to be up to 80% (Iversen et al, 2004a;Drudy et al, 2006;Friedemann, 2009), and cases in infants have been epidemiologically-linked to the consumption of reconstituted temperature-abused powdered infant formula (Himelright al., 2002;Beuchat et al, 2009). More recently, Patrick et al (2014) surveyed clinical data from 544 Cronobacter infections obtained from six of ten USA FoodNet sites, and reported that Cronobacter infections are more common in adults than in infants; a finding that was not previously appreciated by many infectious disease experts. The infections reported among adults include nosocomial-and community-acquired urinary tract infections, septicemia, pneumonia, and catheter-associated wound infections.…”
Section: Introductionmentioning
confidence: 99%
“…Os casos de meningite foram reportados somente em neonatos e, em muitos casos, o veículo de contaminação foram fórmulas infantis desidratadas (FID) contaminadas pelo patógeno (JASON, 2012). Cronobacter tem sido isolada de uma grande variedade de outras infecções, como enterocolite necrosante (LAI 2001), infecções pulmonares (SEE et al, 2007), infecções urinárias (BHAT et al, 2009;PATRICK et al, 2014) e colecistite aguda (TSAI et al, 2013). Contudo, na grande maioria destes casos, não foi comprovado que o Cronobacter era efetivamente o responsável pela infecção, uma vez que outros micro-organismos também foram identificados no sítio da infecção (FARMER 3rd, 2015).…”
Section: Introductionunclassified
“…Cronobacter strains are opportunistic pathogens that can cause serious infections in neonates, including meningitis, necrotising enterocolitis and sepsis with low frequency, but high lethality rate (Hunter and Bean 2013;Holy and Forsythe 2014). Infections in adults also have been reported, in particular among the elderly and immunocompromised patients (Patrick et al 2014;Alsonosi et al 2015).…”
Section: Introductionmentioning
confidence: 99%